2012
DOI: 10.1038/aps.2012.6
|View full text |Cite
|
Sign up to set email alerts
|

Breviscapine inhibits high glucose-induced proliferation and migration of cultured vascular smooth muscle cells of rats via suppressing the ERK1/2 MAPK signaling pathway

Abstract: Aim: To investigate the influences of breviscapine, a flavonoid extracted from Erigeron breviscapus, on the proliferation and migration of vascular smooth muscle cells (VSMCs) cultured in a high glucose medium and the underlying mechanisms. Methods: VSMCs were isolated from thoracic aortas of male Sprague-Dawley rats and cultured in vitro. Cell proliferation was evaluated using Counting Kit-8 cell viability assay. Cell migration was evaluated using transwell migration assay and in vitro scratch assay. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 29 publications
2
33
0
1
Order By: Relevance
“…As different phosphorylation site of Cx43 like Ser 368 and Ser 255 (Warn‐Cramer et al, ; Chung et al, ) might result in different GJIC coupling, it might be the limitation of our study for lack of further exploration on exact effect of P1 and P2. By Western blotting, we observed that HG elevated both phosphorylation level of PKC and Erk MAPKs, but P38 and JNK MAPKs were not activated, which was similar with recent reports about HG treatment in vascular smooth muscle cells (Yang et al, ; He et al, ). Although our result indicated the transient PKCα/β2 activation by high glucose, with pretreatment of the PKC and Erk inhibitors for 30 min, we noticed that only PKC inhibitor, GF109203X nearly abolished the suppression effect of HG on Cx43, including P0, P1, and P2, while PD98059 (20 µM) showed no significant difference.…”
Section: Discussionsupporting
confidence: 91%
“…As different phosphorylation site of Cx43 like Ser 368 and Ser 255 (Warn‐Cramer et al, ; Chung et al, ) might result in different GJIC coupling, it might be the limitation of our study for lack of further exploration on exact effect of P1 and P2. By Western blotting, we observed that HG elevated both phosphorylation level of PKC and Erk MAPKs, but P38 and JNK MAPKs were not activated, which was similar with recent reports about HG treatment in vascular smooth muscle cells (Yang et al, ; He et al, ). Although our result indicated the transient PKCα/β2 activation by high glucose, with pretreatment of the PKC and Erk inhibitors for 30 min, we noticed that only PKC inhibitor, GF109203X nearly abolished the suppression effect of HG on Cx43, including P0, P1, and P2, while PD98059 (20 µM) showed no significant difference.…”
Section: Discussionsupporting
confidence: 91%
“…Interest in its versatile protective effects in cardiovascular and cerebral diseases has been growing over the last decade. [34][35][36][37][38][39][40] Scutellarin, the major flavonoid component extracted from Dengzhanxixin, is known to exhibit potent cardiovascular and neuronal effects. 41) However, since it was discovered that scutellarein, one of the main in vivo metabolites of scutellarein, has a higher bioavailability than scutellarein, 15) its pharmacological activities have attracted more attentions.…”
Section: Discussionmentioning
confidence: 99%
“…Breviscapine , one plant flavonoids found from Erigeron breviscapus , could dilate brain blood vessels, increased cerebral blood flow and cardiac coronary flow, reduce blood viscosity, and improve microcirculation [34]. Traditionally it has been used for thousand years.…”
Section: Discussionmentioning
confidence: 99%